Identification of a Novel Bone Marrow Cell-Derived Accelerator of Fibrotic Liver Regeneration Through Mobilization of Hepatic Progenitor Cells in Mice. (31st October 2018) - Yanagawa, Takayo; Sumiyoshi, Hideaki; Higashi, Kiyoshi; Nakao, Sachie; Higashiyama, Reiichi; Fukumitsu, Hiroshi; Minakawa, Kaori; Chiba, Yosuke; Suzuki, Yuhei; Sumida, Kayo; Saito, Koichi; Kamiya, Akihide; et al.
Abstract : Granulocyte colony stimulating factor (G-CSF) has been reported to ameliorate impaired liver function in patients with advanced liver diseases through mobilization and proliferation of hepatic progenitor cells (HPCs). However, the underlying mechanisms remain unknown. We previously showed that G-CSF treatment increased the number of bone marrow (BM)-derived cells migrating to the fibrotic liver following repeated carbon tetrachloride (CCl4 ) injections into mice. In this study, we identified opioid growth factor receptor-like 1 (OGFRL1) as a novel BM cell-derived accelerator of fibrotic liver regeneration in response to G-CSF treatment. Endogenous Ogfrl1 was highly expressed in the hematopoietic organs such as the BM and spleen, whereas the liver contained a relatively small amount of Ogfrl1 mRNA. Among the peripheral blood cells, monocytes were the major sources of OGFRL1. Endogenous Ogfrl1 expression in both the peripheral blood monocytes and the liver was decreased following repeated CCl4 injections. An intrasplenic injection of cells overexpressing OGFRL1 into CCl4 -treated fibrotic mice increased the number of HPC and stimulated proliferation of hepatic parenchymal cells after partial resection of the fibrotic liver. Furthermore, overexpression of OGFRL1 in cultured HPC accelerated their differentiation as estimated by increased expression of liver-specific genes such as hepatocyte nuclear factor 4α, cytochrome P450, and fatty acid binding protein 1, although it did not affect the colony forming ability of HPC. These results indicate a critical role of OGFRL1 in the mobilization and differentiation of HPC in the fibrotic liver, and administration of OGFRL1-expressing cells may serve as a potential regenerative therapy for advanced liver fibrosis. Stem Cells   2019;37:89–101 : Abstract : Intrasplenic administration of bone marrow mesenchymal stem cells (MSC) overexpressing opioid growth factor receptor-like 1 into carbon tetrachloride (CCl4 )-induced fibrotic mice increased the number of α-fetoprotein (AFP)-positive cells with active bromodeoxyuridine (BrdU) uptake and that of proliferating parenchymal hepatocytes following 70% partial resection of the fibrotic liver.